FAKTOR PERSALINAN KALA 1 LAMA DI PUSKESMAS KETUWAN BLORA - Dwi Susilowati; Dewi Andang Prastika; Listyaning Eko Martanti (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2021)
The first stage of labor includes a prolonged latent phase and a prolonged active phase. Long-term delivery always poses risks and complications for both the mother and the fetus in her womb and can be fatal if not treated properly. Based on data from Ketuwan Health Center from January 2020 to December 2020, there were 37 cases of prolonged first stage labor out of 159 cases of labor. The purpose of this study was to determine the factors associated with the incidence of prolonged first stage of labor at the Ketuwan Health Center, Blora Regency which included maternal age, education, parity, his and the weight of the fetus. This type of research is quantitative analytic with a case control research design, using a retrospective approach and using a proportional random sampling technique. The number of samples was 37 cases and 37 controls. Data analysis was carried out univariate and bivariate using the Odds Ratio test. The results showed that the factors associated with the incidence of prolonged first stageof labor were Age (p=0.403; OR=2.121), Education (p=0.627; OR=0.789), Parity (p=0.011; OR=3.544), Contraction (p= 0.000; OR=0.072), Fetal Weight (p=1,000; OR=1,000). The conclusion of this study is that the factors associated with the incidence of prolonged first stage labor include parity and his, while age), education, and fetal weight do not have a significant relationship with the incidence of prolonged first stage labor. The advice given is to establish a definite diagnosis and make the right decisions to reduce the risk to the mother and fetus